Upaya dalam Pemerataan Pendidikan di Daerah Terpencil - Yudha Maya Septiana; Solfema Solfema; Lili Dasa Putri (Jurnal Kajian dan Penelitian Umum, 2024)
The disparity in educational access in Indonesia, particularly in remote areas, poses a significant challenge to the development of human resources nationwide. This article highlights the crucial role of education in unlocking individual potential and explores efforts to improve equal access to education across all regions of Indonesia. A literature review methodology is employed to examine the factors contributing to this educational inequality, including physical barriers, economic constraints, inadequate facilities, curriculum quality gaps, and technological disparities. The article also discusses the negative impacts of unequal educational access, such as economic stagnation and social inequality. Through empowerment initiatives, collaboration with the government, capacity building for educators, and active community involvement, solutions to achieve more equitable education in remote areas can be realized.